IBN THUFAIL'S PHILOSOPHICAL THOUGHTS IN THE STORY OF HAYY BIN YAQDZON - Iqbal, Moch; Mukaromah, Melisa (Living Islam: Journal of Islamic Discourses, 2023)
Abstract The purpose of this study is to examine and explain and convey his philosophical thoughts in various aspects through the story of Hayy bin Yaqdzon. Therefore researchers are interested in conducting in-depth research on how the philosophical thoughts of Ibn Thufail are contained in the story of Hayy bin Yaqdzon. This research uses the Library Research method (literature study) with qualitative descriptive. As a result of this research, the researcher concludes that the philosophical thoughts of Ibn Thufail contained in the story of Hayy bin Yaqdzon include ontological aspects regarding nature and being (Hayy bin Yaqdzon's origins, matter and form as well as arguments proving the existence of God), epistemological aspects regarding sources of knowledge (mind). , five senses and revelation) as well as axiological aspects including ethics (towards God, environment and social). Keywords: Philosophical Thought, Ibn Thufail, Acts, Hayy bin Yaqdzon.